2016
DOI: 10.1088/0957-4484/27/8/085101
|View full text |Cite
|
Sign up to set email alerts
|

Modulating macrophage polarization with divalent cations in nanostructured titanium implant surfaces

Abstract: Nanoscale topographical modification and surface chemistry alteration using bioactive ions are centrally important processes in the current design of the surface of titanium (Ti) bone implants with enhanced bone healing capacity. Macrophages play a central role in the early tissue healing stage and their activity in response to the implant surface is known to affect the subsequent healing outcome. Thus, the positive modulation of macrophage phenotype polarization (i.e. towards the regenerative M2 rather than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 37 publications
2
102
0
1
Order By: Relevance
“…[10][11][12] Although rapid physiological resolution of inflammation is conducive to tissue healing, continued chronic inflammation would result in the hyperplasia of fibrotic scar tissue, ultimately leading to implant failure. 13,14 Therefore, it would also be beneficial for early tissue healing and implant success to control the inflammatory process through macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Although rapid physiological resolution of inflammation is conducive to tissue healing, continued chronic inflammation would result in the hyperplasia of fibrotic scar tissue, ultimately leading to implant failure. 13,14 Therefore, it would also be beneficial for early tissue healing and implant success to control the inflammatory process through macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, M1 activated macrophages could be re-educated into the M2 phenotype, and vice versa, by further changes in the stimuli. This process is referred to as macrophage reprogramming or repolarization [33,34]. …”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…TiO 2 NPs are of significant concern in the field of implants because titanium metal resists corrosion from the body. The expression of M2 subtype markers (Arg1, MR, and CD163) was markedly increased on the surface of bioactive ion Ca and Sr-modified nanostructured Ti implants [33]. Further studies showed that surface bioactive ion modification on the nanotopography of Ti implants plays an important role in inducing M2 macrophage polarization by modulating the shape and spread of adherent macrophages.…”
Section: Nps Modulate Macrophage Polarization and Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because metals exhibit high strength, which minimises the possibility of experiencing major failures. Therefore, they have been the main choice of hermetic seals of large biomedical implants such as pacemakers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%